The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.12735/ier.v2i1p33
|View full text |Cite
|
Sign up to set email alerts
|

Improving Pre-Service Teachers’ Attitudes towards Individuals with Mental Illness through an Introduction to Special Education Course

Abstract: Mental illness in children and adults continues to be a controversial and misunderstood topic. Previous research has examined different populations' attitudes toward mental illness, and efforts to change community attitudes toward individuals with mental illness have included contact with the mentally ill and education programs. However, little research has examined teachers' attitudes toward the mentally ill, nor programs for positively impacting those beliefs. The purpose of the present study was to first as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(19 reference statements)
1
1
0
Order By: Relevance
“…Relevant and scientific proven knowledge, practical intervention sessions, direct contact with people with special needs tend to improve perceptions and attitudes, diminish misinformation and prejudice, discrimination and stigma. This finding sustains the importance of initial formal training in improving attitudes and behaviors towards special groups (Maag et al, 2014;Predescu et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…Relevant and scientific proven knowledge, practical intervention sessions, direct contact with people with special needs tend to improve perceptions and attitudes, diminish misinformation and prejudice, discrimination and stigma. This finding sustains the importance of initial formal training in improving attitudes and behaviors towards special groups (Maag et al, 2014;Predescu et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…This perception is considered as one of the main constraints to the introduction of prevention programmes against SM within schools for SWDs. The study participants were future teachers, and many studies have indicated the importance of teachers’ perceptions in improving services [ 25 ]. Graham, Phelps, Maddison, and Fitzgerald [ 26 ] reported that teachers’ perceptions played a key role in the significance they placed on schools enhancing students’ mental health.…”
Section: Discussionmentioning
confidence: 99%